Investigation of dirofilariasis among dog population in dog shelter, Pekan Nanas - Winniesa Pi Chit. (2017)
As a result of globalization and climate change, Dirofilaria immitis and Dirofilaria repens are the most common species of filarial mematodes found in dogs. Dirofilariasis is a potential zoonotic disease that may be transmitted to human. There is limited study conducted regarding canine dirofilariasis in dog population in Malaysia. Hence, this study is to detect filarial parasites, i.e. Dirofilaria immitis. Dirofilaria repens and Brugia malayi in shelter dogs that located in Pekan Nanas, Johor. A single-step multiplex polymerase chain reaction (PCR) was performed by targeting at amplifying the internal transcribed spacer-2 (ITS-2) region of extracted DNA to detect and differentiate between the three species of filarial parasites. Blood sample from 40 dogs were collected from a shelter. 20/40 dogs were given monthly oral Ivermectin and doxycycline and another 20 dogs were not on any heartworm prevention. The prevalence of difofilariasis in forty dogs was 17.55 (7/40). All positive samples were suggestive of Dirofilaria immitis with four female and three male dogs respectively. Further sequencing at the (ITS-2) region is recommended to confirm the filarial genotype. All the affected dogs were found in the group that did not receive any heartworm prevention. Implementation of heartworm prevention is important in shelter management.